FRACTURES CAUSES AND TYPES DESCRIPTION IN DRAJAT PRAWIRANEGARA HOSPITAL SERANG INDONESIA - Omat Rachmat; Ilma Fiddiyanti (Fakultas Kedokteran Gigi Unjani, 2023)
Fractures are often associated with considerable morbidity, leading to extended hospital stays. Disturbances due to fractures impact activity tolerance, thereby reducing productivity. Fracture is a term for loss of continuity of bone or cartilage, either total or partial. In general, a fracture is caused by trauma or physical exertion. This case report consists of four types of fractures in the Drajat Prawiranegara Hospital Serang Indonesia: transverse fractures, cumulative fractures, oblique, segmental, impacted, and spiral fractures. Causes of fractures can be divided into traumatic injuries, direct, indirect, sudden violent contractions, pathological fractures, bone tumours, chronic infections, rickets, and term bone stress. The gold standard examination used to determine the location, type, and severity is an x-ray radiology examination. DOI : 10.54052/jhds.v3n2.p217-226